Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1038/sj.npp.1301647
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Phencyclidine Administration Selectively Reduces Adult Cortical Parvalbumin-Containing Interneurons

Abstract: Transient postnatal NMDA receptor blockade by phencyclidine (PCP), ketamine, or MK-801 induces developmental neuroapoptosis and adult behavioral deficits, which resemble abnormal human behaviors typically present in schizophrenia. This study tested the hypothesis that PCP-induced developmental apoptosis causes a specific deficit of GABAergic interneurons containing parvalbumin (PV), calretinin (CR), or calbindin (CB). Young adult (PND56) rats that were given a single dose of PCP (10 mg/kg) on PND7 exhibited no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 106 publications
7
96
1
Order By: Relevance
“…Thus, prenatal immune challenge at E9 affects PV in the PFC, while similar insult at E17 impacts PV in both PFC and VH (Meyer et al, 2008). Likewise, blockade of NMDAR at prenatal, postnatal, adolescent or adult age does not impact PV-IR FSI in the same way and same brain structures (Abekawa et al, 2007;Wang et al, 2008;Zhang et al, 2008). A GSH deficit has also region-and time-specific effects on PV-IR FSI, causing reduction of PV-IR FSI in the VH of adults but affecting also postnatal maturation of PV FSI in the anterior cingulate cortex (Cabungcal et al, 2006;Do et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, prenatal immune challenge at E9 affects PV in the PFC, while similar insult at E17 impacts PV in both PFC and VH (Meyer et al, 2008). Likewise, blockade of NMDAR at prenatal, postnatal, adolescent or adult age does not impact PV-IR FSI in the same way and same brain structures (Abekawa et al, 2007;Wang et al, 2008;Zhang et al, 2008). A GSH deficit has also region-and time-specific effects on PV-IR FSI, causing reduction of PV-IR FSI in the VH of adults but affecting also postnatal maturation of PV FSI in the anterior cingulate cortex (Cabungcal et al, 2006;Do et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem studies on schizophrenia patients report a decreased PV expression in the prefrontal cortex and hippocampus (Beasley et al, 2002;Hashimoto et al, 2003;Knable et al, 2004). In addition, numerous animal models also report region-specific decreases in PV expression (Amitai et al, 2012;Chen et al, 2014;Francois et al, 2009;Jenkins et al, 2010;Lodge et al, 2009a;Penschuck et al, 2006;Wang et al, 2008). Moreover, we have recently demonstrated that a decrease in PV interneuron function is sufficient to augment hippocampal signaling and produce downstream changes in dopamine system function and behavior (Boley et al, 2014;Shah and Lodge, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthemore, atypical antispsychotics reverse these impairments. These biochemical and behavioral changes phenotipically resemble observations seen in schizophrenia and may serve as a model of the development of schizophrenia (Broberg et al, 2008, Wang et al, 2008. Finally, Dizocilpine (MK801) is frequently used as an animal model of schizophrenia (Fletcher et al, 1989).…”
Section: Pharmacological Approachesmentioning
confidence: 99%